Optimizing Course Offerings in a Science Department - Yu Kay Law (Academic Chairpersons Conference Proceedings, 2023)
We will discuss how enrollment data and faculty/advisor input can be used to maximize schedule efficiency in course offerings and providing for student success. We will also discuss how best to monitor and rearrange course schedules in light of actual enrollment.
Keywords: scheduling; enrollment management; low-enrolled sections; planning; faculty